HUBUNGAN KELUARGA BROKEN HOME DENGAN PERILAKU AGRESIF DI SMK NUR AZIZI TANJUNG MORAWA - Panny Chintya; Dina Hidayati Hutasuhut; Nur Asyah; Ika Sandra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The family is the first and main socialization institution that plays an important role in shaping the character and social behavior of children. However, if the family condition is not harmonious or there is a split (broken home), this can have a negative impact on the psychological development of children. One of the impacts that often appears is aggressive and antisocial behavior. This study aims to determine the relationship between the condition of the Broken Home family and aggressive behavior in students at SMK Nur Azizi Tanjung Morawa. This study uses a quantitative approach with a structured correlational design that has been tested for validity and reliability. The study population was 88 students, and the sampling technique used purposive sampling based on certain criteria, so that 30 appropriate respondents were obtained. Data collection was carried out through the Broken Home Family Scale and the Aggressive Behavior Scale. The results of data analysis using the Pearson product moment correlation test showed that there was a significant relationship between the condition of the Broken Home family and aggressive behavior of students, with a significance value (p) of 0.000 (p <0.05) and a correlation coefficient (r) of 0.382. This finding shows that the more disharmonious the family condition, the higher the tendency for aggressive behavior in students. Therefore, special attention is needed from schools and families in providing emotional support to students from broken homes, so that they can manage their emotions more healthily and develop positive social behavior.